2008
DOI: 10.2203/dose-response.07-024.rithidech
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Radiation Hormesis after In Vitro Exposure of Human Lymphocytes to Low Doses of Ionizing Radiation

Abstract: h Previous research has demonstrated that adding a very small gamma-ray dose to a small alpha radiation dose can completely suppress lung cancer induction by alpha radiation (a gamma-ray hormetic effect). Here we investigated the possibility of gamma-ray hormesis during low-dose neutron irradiation, since a small contribution to the total radiation dose from neutrons involves gamma rays. Using binucleated cells with micronuclei (micronucleated cells) among in vitro monoenergetic-neutron-irradiated human lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 58 publications
0
38
0
1
Order By: Relevance
“…The lack of any other effects due to pre-conditioning with LDR irradiation prior to sSPE exposure was somewhat unexpected, since many studies have demonstrated induction of protection by low-dose radiation against a subsequent high-dose radiation event (26,(44)(45)(46). Radioadaptation apparently can occur in cells hit directly by radiation or as a consequence of the "bystander effect," i.e., interaction with substances released by the hit cells and/ or by direct contact with them (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of any other effects due to pre-conditioning with LDR irradiation prior to sSPE exposure was somewhat unexpected, since many studies have demonstrated induction of protection by low-dose radiation against a subsequent high-dose radiation event (26,(44)(45)(46). Radioadaptation apparently can occur in cells hit directly by radiation or as a consequence of the "bystander effect," i.e., interaction with substances released by the hit cells and/ or by direct contact with them (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…However, this system essentially ignores natural radiation protection and in doing so can lead to radiation-phobia associated casualties during radiological emergencies. Based on the material discussed herein and elsewhere (Ketchum 1987;Wolf et al 1988;Wolff 1989Wolff , 1992Wolff , 1996Luckey 1991;Mifune et al 1992;Hipp and Bauer 1997;Trosko 1998;Redpath et al 2001;Liu 2003;Sakai et al 2003;Scott 2004Scott , 2005Scott , 2007Scott , 2008Jaworowski 2006;Bauer 2007;Day et al 2007;Feinendegen 2005;Sakai 2006;Scott and Di Palma 2006;Feinendegen et al 2007;Liu 2007;Mitchel 2007;Portess et al 2007;;Strzelczyk et al 2007;Cohen 2008;Rithidech and Scott 2008;Sanders 2008;Sanders and Scott 2008;Scott et al 2008;Tubiana 2008), there is a need for a more scientifically valid, updated system of radiation protection that allows for radiation ANP. However, current radiation protection organizations continue to promote the LNT-based system in spite of its problems (Strzelczyk et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…High-LET alpha radiation does not appear to effectively activate the PAM process . For exposure to neutrons, the gamma-ray component to the dose appears to activate the PAM process and thereby protect from deleterious neutron-induced stochastic effects (Rithidech and Scott 2008). The level of protection appears to increase as the gamma-ray contribution to the dose increases, which depends on neutron energy (Rithidech and Scott 2008).…”
Section: Low-dose-radiation Stimulated Protective Apoptosis Medicatedmentioning
confidence: 99%
“…This led to the inference that low dose radiation exhibits beneficial effects (hormetic effects), while high dose radiation exhibits toxic effects. The results also showed that previous exposure to low doses (≤10 cGy) of radiation reduces subsequent response (adaptive protection) (Azzam et al 1994;Feinendegen 2005;Day et al 2007;Rithidech and Scott 2008;Rithidech 2012a;Doss 2014) and stimulates immunity (Liu 2007;Yu et al 2013). Currently, the exact molecular mechanisms associated with radiationinduced adaptive protection remain unclear, although several signaling pathways have been proposed (Tang and Loke 2015).…”
Section: Introductionmentioning
confidence: 94%
“…It also has been found that small doses of radiation induce "protective bystander effects", not "deleterious bystander effects," as seen at high doses (Rithidech and Scott 2008). Further, small doses of radiation are incapable of inducing late-occurring damage (normally known as "genomic instability") (Rithidech et al 2012a andb, 2013).…”
Section: Introductionmentioning
confidence: 99%